Public Ideas: Their Varieties and Careers. Issue 3 (June 2019) - Hallett, Tim; Stapleton, Orla; Sauder, Michael
In light of ongoing concerns about the relevance of scholarly activities, we ask, what are public ideas and how do they come to be? More specifically, how do journalists and other mediators between the academy and the public use social science ideas? How do the various uses of these ideas develop over time and shape the public careers of these ideas? How do these processes help us understand public ideas and identify their various types? In addressing these questions, we make the case for a sociology of public social science. Using data from newspaper articles that engage with seven of the most publicly prominent social science ideas over the past 30 years, we make three contributions. First, we advance a pragmatic, cultural approach to understanding public ideas, one that emphasizes fit-making processes and applicative flexibility. Second, we define public ideas: social science ideas become public ideas when they are used as objects of interest (being the news), are used as interpretants (making sense of the news), and ebb and flow between these uses as part of an unfolding career. Third, we construct a typology of public ideas that provides an architecture for future research on public social science.